Myths and legends from ancient Greece and around the world. (Upper Saddle River, NJ : Prentice Hall, 2000)
A collection of folklore from around the world.
Classical myths -- Norse myths and Medieval legend -- Myths from around the world.
Keywords: Mythology, Greek -- Juvenile literature; Mythology -- Juvenile literature